Analisis Kelaikan Fungsi Bangunan Gedung Rumah Sakit Ibu dan Anak Nirmala Kediri - Irfan, Ahmad; Oetomo, Wateno (Portal: Jurnal Teknik Sipil, 2024)
Indonesia is a developing country which is currently actively carrying out development, both physical development such as buildings, bridges, roads, ports and other physical development as well as non-physical development such as mental rehabilitation. The suitability of a building is a requirement that must be met to obtain a functionally fit certification. Fulfillment of eligibility has several requirements such as safety, health, comfort and convenience. The Nirmala Mother and Child Hospital building is located on Jalan Attorney General Suprapto, Kediri City, East Java. Based on the results of interviews with project supervisors and direct observations in the field, building planning does not refer to the Minister of Health Regulation. This study aims to evaluate the comparison of the existing spatial layout of the Nirmala Mother and Child Hospital with Minister of Health Regulation No. 40 of 2022. Results of the evaluation of the building's functional suitability evaluation based on Minister of Health Regulation No. 40 of 2022 on the spatial layout of the Nirmala Kediri Mother and Child Hospital has met the spatial planning requirements according to the Minister of Health, but with the caveat that there must be an additional waiting room in each examination and treatment room.